A Preliminary Psychometric Investigation of a Chinese Version of the Engaged Teachers Scale (C-ETS) - Ho, Sammy K.; Chan, Hang; Chan, Edmund Sze-Shing; Fung, Kwok-Kin; Hung, Shirley Suet-Lin (Frontiers in Education, 2021)
This study examines the psychometric properties of a Chinese version of the Engaged Teacher Scale (C-ETS). A translated questionnaire with 16 items was administered to a sample of 341 primary and secondary school teachers in Hong Kong. A series of confirmatory factor analyses were performed to assess the construct, convergent, and discriminant validity of the scale in alternative models. Results provide support for a second-order model with teacher engagement as an overarching construct with four hypothesized dimensions: emotional engagement, cognitive engagement, social engagement (students), and social engagement (colleagues). The C-ETS provides a useful measure for teacher engagement in Chinese societies. Contributions and limitations of the study are discussed.